(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The essay aims to investigate the legitimacy of the employment of third-party service providers within clinical trials on medicinal products for human use. Through a constant referral to the current legal framework, and also thanks to the experience developed during the Covid-19 pandemic, two critical profiles of particular note will be examined, and some insights on the investigator’s liability will be provided. To the outcome, a de iure condendo solution to the arisen criticalities will be suggested, also in order to enhance the potential offered by the shared care planning model.